2000
DOI: 10.1007/s002680010222
|View full text |Cite
|
Sign up to set email alerts
|

Complications of Laparoscopic Adrenalectomy: Results of 169 Consecutive Procedures

Abstract: Laparoscopic adrenalectomy (LA) has become the gold standard for adrenalectomy. Review of the literature indicates that the rate of intra- and postoperative complications is not negligible. The aim of this study was to evaluate the complications observed in a series of 169 consecutive LAs performed at a same center for a variety of endocrine disorders. Between June 1994 and December 1998 a series of 169 LAs were performed in 159 patients: 149 unilateral LAs and 10 bilateral LAs. There were 98 women and 61 men … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
61
1
8

Year Published

2003
2003
2020
2020

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 150 publications
(75 citation statements)
references
References 18 publications
5
61
1
8
Order By: Relevance
“…Indications for operations in this study were similar to those in published series, in which most of the operations were performed for aldosteronomas, glucocorticoid excess, pheochromocytomas, and incidentalomas 10,11 .…”
Section: Discussionsupporting
confidence: 66%
“…Indications for operations in this study were similar to those in published series, in which most of the operations were performed for aldosteronomas, glucocorticoid excess, pheochromocytomas, and incidentalomas 10,11 .…”
Section: Discussionsupporting
confidence: 66%
“…12 It is the likelihood of malignancy and local invasion associated with large tumor size that make it sometimes difficult to be removed laparoscopically, not the size per se. 13,14 The operative time was reported by some authors to be significantly longer in laparoscopic adrenalectomy, however, this was not the case in our study. 7,16 We found that the optic magnification in laparoscopy and the clarity of anatomy made the dissection and adrenal vessels control much easier and faster.…”
Section: Discussioncontrasting
confidence: 56%
“…Laparoscopic adrenalectomy is highly effective in the ectopic ACTH syndrome (2) and occasionally in Cushing's disease, but its use may cause unnecessary or inappropriate delay. Patients should be referred in a timely fashion to a facility where appropriate laparoscopic surgical expertise exists.…”
Section: Introductionmentioning
confidence: 99%